Meningkatkan Minat Baca dan Literasi Melalui Pojok Baca di SMP PGRI Pulau Salemo: en - Rusli Ismail; Ady Rukma; Aminuddin; Muhammad Hasim; Muh Yusuf Aldifari (Program Studi Sarjana Terapan PTM FT UNM, 2024)
The teaching campus is part of MBKM which provides opportunities for students to learn to become teacher partners and help with literacy and numeracy learning at assigned schools, one of which is PGRI Salemo Island Middle School, Liukang Tupabbiring Utara District, Pangkajene Islands Regency, South Sulawesi Province. The literacy program carried out at PGRI Salemo Island Middle School is one of the work programs of student activities. This program includes activities such as creating a reading corner, book reading, creative writing, book discussions and other literacy activities. This research used a qualitative method by conducting direct observations at the implementation location in coordination with the school, as well as field supervisors for students. The results of the observations found that students needed school facilities to be used as reading facilities. Therefore, to overcome this problem through the Teaching Campus program, it is done by creating a reading corner in the classroom which is hoped to build a culture of student literacy.